2018
DOI: 10.1177/0271678x18780130
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiome primes a cerebroprotective immune response after stroke

Abstract: Microbiome alterations have been shown to affect stroke outcome. However, to what extent the presence of a gut microbiome per se is affecting post-stroke neuroinflammation has not been tested. By comparing germfree mice with recolonized (Ex-GF) and conventional SPF mice, we were able to demonstrate that bacterial colonization reduces stroke volumes. Bacterial colonization increased cerebral expression of cytokines as well as microglia/macrophage cell counts in contrast to improved stroke outcome. Interestingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 8 publications
5
100
0
Order By: Relevance
“…In the first 2-3 days after AIS, lymphocytes arrive at the ischemic lesion (adaptive response) ( 4 ). In particular, T helper-1 and-17 subpopulations activate neuroinflammation, whereas regulatory T-cells have a neuroprotective action due to their anti-inflammatory properties ( 50 ). The consequences of this remain unclear, as detrimental effects to regulatory T cells after AIS have been reported ( 51 ).…”
Section: Pathophysiologymentioning
confidence: 99%
“…In the first 2-3 days after AIS, lymphocytes arrive at the ischemic lesion (adaptive response) ( 4 ). In particular, T helper-1 and-17 subpopulations activate neuroinflammation, whereas regulatory T-cells have a neuroprotective action due to their anti-inflammatory properties ( 50 ). The consequences of this remain unclear, as detrimental effects to regulatory T cells after AIS have been reported ( 51 ).…”
Section: Pathophysiologymentioning
confidence: 99%
“…Previous findings have shown that the induction of stroke in murine models of brain ischemia can activate immune cells and promote the progression of inflammatory heart disease . Moreover, brain injury can modulate the functions of the intestine and its immune components, supporting the hypothesis of multi-organ failure after stroke (Singh et al, 2016a;Singh et al, 2018). In addition, stroke patients may present signs of severe immunosuppression and inflammation that often lead to hospital-acquired respiratory infections (Shi et al, 2018).…”
Section: Introductionmentioning
confidence: 78%
“…This is a relationship that is fraught with peril as a nuanced system of checks and balances are required to limit invasive flora whilst restraining overtly inflammatory responses and allowing the host to reap the benefits of housing a commensal community. As a consequence of this intimate host-microbe relationship, it is unsurprising that shifts in the microbial communities inhabiting barrier surfaces are associated with disease states during inflammation, injury and aging (204207). In this context, metabolites generated by the gastrointestinal microbial community have been demonstrated to calibrate homeostatic and anti-microbial immune networks in situ (208211).…”
Section: Possible Mechanisms By Which Periodontitis Could Contributementioning
confidence: 99%